The development of a healing model of care for an Indigenous drug and alcohol residential rehabilitation service: a community-based participatory research approach - Alice Munro; Anthony Shakeshaft; Anton Clifford (BMC, 2017)
Abstract Background Given the well-established evidence of disproportionately high rates of substance-related morbidity and mortality after release from incarceration for Indigenous Australians, access to comprehensive, effective and culturally safe residential rehabilitation treatment will likely assist in reducing recidivism to both prison and substance dependence for this population. In the absence of methodologically rigorous evidence, the delivery of Indigenous drug and alcohol residential rehabilitation services vary widely, and divergent views exist regarding the appropriateness and efficacy of different potential treatment components. One way to increase the methodological quality of evaluations of Indigenous residential rehabilitation services is to develop partnerships with researchers to better align models of care with the client's, and the community's, needs. An emerging research paradigm to guide the development of high quality evidence through a number of sequential steps that equitably involves services, stakeholders and researchers is community-based participatory research (CBPR). The purpose of this study is to articulate an Indigenous drug and alcohol residential rehabilitation service model of care, developed in collaboration between clients, service providers and researchers using a CBPR approach. Methods/Design This research adopted a mixed methods CBPR approach to triangulate collected data to inform the development of a model of care for a remote Indigenous drug and alcohol residential rehabilitation service. Results Four iterative CBPR steps of research activity were recorded during the 3-year research partnership. As a direct outcome of the CBPR framework, the service and researchers co-designed a Healing Model of Care that comprises six core treatment components, three core organisational components and is articulated in two program logics. The program logics were designed to specifically align each component and outcome with the mechanism of change for the client or organisation to improve data collection and program evaluation. Conclusion The description of the CBPR process and the Healing Model of Care provides one possible solution about how to provide better care for the large and growing population of Indigenous people with substance.